Avaliação do desenvolvimento de capim-citronela (cymbopogon winterianus) irrigado com três diferentes tipos de efluentes - Gaspar, Gabriel Vidal (2017)
The use of domestic sewage treated for agricultural purposes has been gaining considerable ground in recent years. In addition to providing adequate use of natural resources, practice can improve soil characteristics and enhance agricultural production. However, the effluent is still a possible source of environmental impact, which can cause contamination by microorganisms and also salinize the soil, if there is a good design and operation of the reuse system. In this work, the effluent from an Anaerobic Upflow Reactor, RAFA, followed by an Aerated Submerged Filter, FSA, a Secondary Decanter, and a Contact Tank were used for the irrigation of citronella grass, Cymbopogon winterianus In the irrigation, the water used was supplied by the Water and Sewage Company of Ceará (Cagece), (TA), the treated effluent after the addition of chlorine (TB); and the effluent treated prior to addition of chlorine (TC). Each liquid was applied in seven pots, each pot with two plant seedlings, totalizing seven pots and fourteen plants for each type of effluent. The leaf chlorophyll index was analyzed; dry matter content; the content of inert matter; and some characteristics of the soils in the different vessels, after the period of 115 days. It was observed that the plants irrigated with treated effluents showed a better leaf development and a darker shade of green. In addition, the statistical analyzes of dry mass and inert mass production suggest a higher production of oils when irrigation with treated effluents was performed. The strategy of cultivating the species in irrigated pots with treated effluents can be positive for combating the spread of Dengue fever, Chikungunya fever and Zica, mosquito-related diseases, which are repelled by the plant's oils. Although a palliative measure, the dissemination of the practice can bring benefits to the population, combining the rational use of water resources with the cultivation of strategic plants.